Determination of Vitamin D Concentration in Diabetic and Non Diabetic Men and Its Correlation with Age - Abdulhadi M. Jumaa; Meqdam Atiyah Khalaf; Hassan Yashar Hassan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background Vitamin D is synthesized from precursors” present at the surface of the epidermis and then undergo biotransformation which achieved at the hepatocytes and finally by hydroxylation enzymes in the nephrons “ . “sunrays play a crucial role in the beginning of D vitamin formation processes, parathyroid hormone is an essential hormone secreted by parathyroid glands and play a key role in the activation of D vitamin by renal alfa hydroxylase”. Food sources of D vitamin are also important for supplementation of human body with some requirements. This Study Aimed to compare the concentration of vitamin D in diabetic patients, and non-diabetic men and its association with age.Patients and Methods the current study started at the beginning of june 2018 and continued until the end of March 2019 , at the outpatient unit in especial private hospital at Tikrit city - Iraq. Eighty men have been enrolled in present study.Results Eighty men were participate in the present study, distributed as 40 non diabetic subjects as controls and 40 diabetic patients. The mean and standerad deviation of D vit. levels of non-insulin dependant diabetes and normal physically fit men show there is significant reduction of D vit. Measurements of the diabetic men patients suffering from T2DM, (13.58 ± 5.29) as compared with control subjects, (19.95 ± 6.5). there are significant decrease of vit. D measurements of T2DM young patients. In T2DM patients less than 18 years old have significant reduction in vitamin D concentration, (13.41 ± 5.1), as compare with T2DM patients aged 18-40 years, (17.23 ± 7.3). Measuremets of D vit. Durind heat season and compare to cold months.The evaluation of D vit. During hot monthes show significant rise(26.4 ± 7.1) in comparison with winter status(13.65 ± 4.2). Conclusions the present study conclude that, D vit. Levels show highly important increament in hot months as compare with winter season and there are significant reduction in the concentration of vitamin D in young age type 2 diabetic patients